PSIKOLOGI DALAM PEMBELAJARAN PAI - Ismail Syakban; Julhadi Julhadi; Yudefrizal Yudefrizal; Hefriyanto Hefriyanto (Jurnal Manajemen Pendidikan, 2026)
Islamic Religious Education (PAI) plays an important role in shaping students who have faith, piety, and noble character. However, the learning process of PAI does not only require the delivery of religious materials but also an understanding of students’ psychological aspects so that Islamic values can be understood, internalized, and practiced in daily life. This paper aims to examine the role of psychology in Islamic Religious Education learning through the integration approach of psychology and Islamic education, psychological approaches in moral education, psychology-based PAI learning strategies, and the process of internalizing Islamic values from the perspective of educational psychology. The method used in this paper is library research by examining various relevant literature sources related to Islamic educational psychology and PAI learning. The results of the study show that the integration of psychology into Islamic education can create a more effective, humanistic learning process that is in accordance with students’ characteristics. The psychological approach in moral education plays a role in shaping behavior through exemplary practices, habituation, motivation, and the development of emotional intelligence. Furthermore, psychology-based PAI learning strategies emphasize the importance of considering individual differences, learning styles, motivation, and students’ emotional conditions. The internalization of Islamic values cannot be achieved merely through knowledge transfer but must involve cognitive, affective, and psychomotor aspects so that religious values become an integral part of students’ personalities.